39.7k views
5 votes
6(3-e) = 42
e =
what does e equal

User Ara Pulido
by
6.1k points

1 Answer

2 votes

Answer:


\boxed{ \bold{ \huge{ \boxed{ \sf{e = - 4}}}}}

Explanation:


\sf{6(3 - e) = 42}

Distribute 6 through the parentheses


\sf{18 - 6e = 42}

Move 18 to right hand side and change it's sign


\sf{ - 6e = 42 - 18}

Subtract 18 from 42


\sf{ - 6e = 24}

Divide both sides of the equation by -6


\sf{ ( - 6e)/( - 6) = (24)/( - 6) }

Calculate


\sf{e = - 4}

Hope I helped!

Best regards!!

User Lorenzo Cutrupi
by
6.3k points